The Effect of Motivation and Trust on Purchasing Intention Netflix in Palembang City - Fandi Chen; Ratna Juwita (Universitas Multi Data Palembang, 2022)
Abstract:This research is analyze the effect of motivation and trust on purchasing intention netflix in Palembang City. The sample in this research are 100 respondent using non purposive sampling. The tool of the analyze is IBM SPSS 22. The result is most of respondent are woman and many respondent are college student and private employee aged 20-24 years old. The result of SPSS are motivation and trust are affect purchasing intention both partial and simultaneous. Abstrak: Penelitian ini menganalisis efek motivasi dan kepercayaan terhadap keputusan pembelian netflix di kota Palembang. Sampel penelitian ini 100 responden menggunakan non purposive sampling. Alat analisis yang digunakan adalah IBM SPSS 22. Hasilnya adalah konsumen netflix di kota Palembang lebih banyak berjenis kelamin perempuan dan berstatus mahasiswa atau pegawai swasta dengan rentang umur 20-24 tahun. Hasilnya adalah motivasi dan kepercayaan berpengaruh positif dan signifikan terhadap keputusan pembelian baik secara parsial maupun simultan